Structural components of readiness of students of non-linguistic faculties for the realization of intercultural communication - Lyubov’ G. Morozkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with the problem of readiness of students of non-linguistic specialties for the realization of intercultural communication in their future professional activity. We are talking about the competitiveness of graduates of non-linguistic universities in the conditions of the modern labor market. Relying on the fact that the notion of “readiness of a person for an activity” is defined by the author not as a temporary state, but as a stable property of a person acting constantly, the author distinguishes three structural components of the readiness of students of non-inguistic faculties to realizе intercultural communication - cognitive (knowledge about the real picture of the world, about the linguistic and cultural picture of the world), technological (ability to communicate in accordance with the cultural characteristics of the native speakers) and reflexive-evaluative (students’ skills to build and analyze the achieved results in the realization of intercultural communication and the motives). In order to form these structural components of readiness, three blocks of student training are identified: content block, technological and resulting blocks. The content block includes the knowledge of the correspondences and differences of cultural and linguistic-cultural facts, traditions, customs, customs of the native culture and the culture of the country of the language being studied. The technological block includes the forms and methods of teaching students of non- linguistic faculties how to realizе intercultural communication. The resulting block contains an evaluation of students’ knowledge and skills by the teacher. The completeness of the cognitive component of student readiness (knowledge of an intercultural nature) was determined by the author using a questionnaire. The completeness of technological and reflexive-evaluative components of the readiness of students of non-linguistic faculties to realizе intercultural communication was determined by assessing the students’ ability to perform intercultural tasks.